2021
DOI: 10.1371/journal.pone.0252639
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and geographical heterogeneity factors associated with poor consumption of foods rich in vitamin A among children age 6–23 months in Ethiopia: Geographical weighted regression analysis

Abstract: Introduction Vitamin A deficiency is a major public health problem in poor societies. Dietary consumption of foods rich in vitamin A was low in Ethiopia. This study aimed to assess the spatial distribution and spatial determinants of dietary consumption of foods rich in vitamin A among children aged 6–23 months in Ethiopia. Methods Ethiopian 2016 demographic and health survey dataset using a total of 3055 children were used to conduct this study. The data were cleaned and weighed by STATA version 14.1 softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
8
1
Order By: Relevance
“…This study's ndings were greater than those of the Kenya DHS 2014 (28%) (22) and Ghana (48%) studies (23).This disparity could be due to socio-demographic and cultural variances. Consistent with previous studies in Ethiopia (14), Tanzania (22) and China (23), animal source foods were the least consumed foods in the last 24 hours of the survey period. Shell sh intake was the least consumed food in the 24 hours leading up to the survey (2.67%), whereas egg consumption was the most consumed food among the study participants (15.5%).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study's ndings were greater than those of the Kenya DHS 2014 (28%) (22) and Ghana (48%) studies (23).This disparity could be due to socio-demographic and cultural variances. Consistent with previous studies in Ethiopia (14), Tanzania (22) and China (23), animal source foods were the least consumed foods in the last 24 hours of the survey period. Shell sh intake was the least consumed food in the 24 hours leading up to the survey (2.67%), whereas egg consumption was the most consumed food among the study participants (15.5%).…”
Section: Discussionsupporting
confidence: 89%
“…Another study conducted in Ethiopia that used the EDHS 2011 data found that undernutration was highly clustered in four areas of Ethiopia, including Amhara and Afar (14,19).The spatial heterogeneity across different regions of Ethiopia might be due to socioeconomic status and demographic factors such as pastoralist regions (Afar and Somali) and the Amhara region (30.8%), low complementary feeding practices, lack of nutritional knowledge, social norms and beliefs, food preferences, and also accessibility and affordability of foods rich in Vitamin A, especially the high cost of animal source foods across these regions of Ethiopia (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparable difference to this finding was observed in a previous study that revealed the consumption of fruits, vegetables, and animal products was increased in people with higher incomes than in those with lower incomes [ 5 , 55 ]. An earlier study in Ethiopia found that low-income households consumed significantly fewer fruits, vegetables, and animal-sourced foods [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though different primary studies have been conducted to assess the nutritional status of children in Ethiopia, none of the previous studies explored the spatial distribution of vitamin A rich foods intake is inadequate, except on poor consumption of vitamin A-rich foods [ 27 ]. Hence, Exploring the spatial patterns and distributions of vitamin A-rich foods intake in the regions of Ethiopia is used for further understanding of where the intake of vitamin A-rich foods among children occurs in a specific location and helps for better nutritional interventions.…”
Section: Introductionmentioning
confidence: 99%